The Hierarchy of Fregean Senses. (12th November 2018) - Simchen, Ori
Abstract : The question whether Frege's theory of indirect reference enforces an infinite hierarchy of senses has been hotly debated in the secondary literature. Perhaps the most influential treatment of the issue is that of Burge (1979 ), who offers an argument for the hierarchy from rather minimal Fregean assumptions. I argue that this argument, endorsed by many, does not itself enforce an infinite hierarchy of senses. I conclude that whether or not the theory of indirect reference can avail itself of only finitely many senses is pending further theoretical development.